The development of a clinical score for the prediction of nonalcoholic steatohepatitis in patients with nonalcoholic fatty liver disease using routine parameters - Chunming, Li; Jianhui, Sheng; Hongguang, Zhang; Chunwu, Qiu; Xiaoyun, Huang; Lijun, Yang; Xuejun, Yu (Turkish Journal of Gastroenterology, 2015)
Abstract Background/Aims: To develop a clinical score for the prediction of nonalcoholic steatohepatitis (NASH) using routine parameters in patients with nonalcoholic fatty liver disease who had abnormal liver function tests and/or fatty liver detected by ultrasonography. Materials and Methods: To identify parameters associated with the presence of NASH by evaluating anthropometric characteristics and routine biomarkers of 82 patients with histologically proven NAFLD and to develop a clinical score for predicting NASH according to the area under the curve of receiver operating characteristics (AUC) of parameters. Results: Four parameters [alanine aminotransferase (ALT), gamma-glutamyl transferase (GGT), C-reactive protein (CRP), and apolipoprotein B (ApoB)/apolipoprotein A1 (ApoA1) ratio] were significantly linked to NASH. The AUROCs of ALT, GGT, CRP, and ApoB/ApoA1 ratio for the prediction of NASH were 0.829, 0.892, 0.708, and 0.712, respectively. The AUROC of the combined clinical score for the prediction of NASH was 0.904 (95% CI, 0.885–1.002) at a cut-off of 3.8 points with a sensitivity of 90.2%, specificity of 87.0%, positive predictive value of 88.3%, and negative predictive value of 91.5%. Conclusion: In the present study, a clinical score was developed for the noninvasive prediction of NASH; the score was based on a combination of routine biochemical parameters and was useful in distinguishing NASH from NAFLD.